A system dynamics analysis of Malaysian palm oil price determinants - Mohammadi, Sahra (2015)
The palm oil industry has made a significant contribution to the Malaysian agricultural sector and has become an important driver in Malaysian economy. In 2011, palm oil accounted for 6% of the GDP and 61.8% of the export value in Malaysia. The industry provides employment to approximately 2.2 mn people, which is the largest in thecountry. Moreover, oil palm cultivation has become an effective means to address rural poverty. Nevertheless, the palm oil price demonstrates volatile behavior and appears with significant fluctuations over time. Price volatility poses risks in the market and affects both producers and consumers. It also hampers economic growth and reduces the stability of returns to firms and investments plus all other parties involved in the palm oil supply chain. It causes direct economic losses, impacts trade competitiveness which diverts trade and investment activities. Thus, understanding the price behavior is vital for the stakeholders of industry. This study, aims to investigate major determinants of Malaysian palm oil price. Based on the relevant literature, this study hypothesizes that the major determinants of palm oil price behavior are the level of production, demand for palm oil, world palm oil price, substitute price such as soybean oil, biodiesel production, and delay in decision making. Understanding the price behavior helps decision makers to become more aware of the possible future trends and turns and enables them to take measures such as inventory and fund management and to reduce the impact of possible shocks into the system. This study employs system dynamics approach to examine the Malaysian palm oil market by using secondary data between 1982 until 2012 reported by government agencies such as Malaysian Palm Oil Board (MPOB) and Ministry of Plantation Industries and Commodities (MPIC). The system dynamics methodology is very relevant for examining the feedback relationships between variables, non-linearity, and delay that exist in a system including the palm oil market. System dynamics simulation helps understand the impact of the market structure, and hence, the behavior of palm oil price both in the short run and long run. A short-run perspective gives opportunities to the industry players to make short term decisions such as taking position in the futures market (hedging) and fund management. In addition, a long-run perspective allows time for them to make long-term decisions such as investment on land capital as well as inventory management. The study found that the palm oil price behavior has been affected by its supply and demand, the world CPO price, and the world soybean oil price. The simulation results indicate that palm oil price will increase by approximately 36.0 percent over the next fifteen years, from RM 2,764/mt in 2012 to RM 4,335/mt in 2030. The price increase attributed to changes in the world palm oil price and an increase in the demand for palm oil products. The study concludes that it is vital for the palm oil industry to monitor the price movement and to keep track closely the changes in the fundamentals particularly CPO production as well as the world CPO and soybean oil prices. Moreover, the Malaysian palm oil industry must develop further value-added products in order to internalize the price changes and to make palm oil ventures economically viable regardless of price changes. To cushion the impact of significant price variability, it is believed that the production and export of biodiesel product can be a major thrust for the palm oil industry in Malaysia.